Gest??o de stakeholders: a influ??ncia da confian??a no ??mbito de projetos - Oliveira, Gilberto Francisco de (2017)
Stakeholders management is perceived as relevant by the academia and practitioners, since not considering all parties with vested interest in a project broadens the possibilities of failures. Stakeholders Management is supported by two main schools, the prescriptive, where activities such as the mapping, identifying and classifying of stakeholders according to their power, interest and the influence they can exert on the project are recommended and, the relational, where links are established, involving and engaging stakeholders throughout the project cycle. There are divergences regarding which school is the most appropriate to the project manager, because there are gaps in both schools. However, even with the practices of both management schools, there is no guarantee of success in a project if there are no trust relationships with the others parties. Trust has a positive relation with the success of projects since the presence of trust relationships reduces conflicts and in a case of crisis, it delivers faster and more effective responses.The attitudes to show empathy, to act transparently benefiting of the other, and to deliver what was promised are put forward as initiatives to build trust in all three types: intuitive, integrity, and competence. In light of the above, this paper proposes to investigate the relations between Stakeholders Management and Trust. We also aim to verify if there is a positive relation between the Prescriptive school and the Relational school and if the Relational is a mediator variable between the Prescriptive and Trust, exerting a positive influence. As a methodological procedure, a quantitative research of hypothetical-deductive approach was chosen. Data collection was done through an online survey, with open and closed questions. It counted on the participation of 130 respondents occupying the position of primary stakeholders in several companies, with a greater participation of the IT, Industry, and Telecommunications segments. For data analysis, the Structural Equation Modeling (SEM) technique and the Partial Least Square (PLS) method was applied using the SmartPLS 3.2.1 software. The results indicated a relevant and significant connection between the Prescriptive and Relational schools, as well as between the Relational and all types of Trust (Intuitive, Integrity and Competence), thus confirming the relevance of Stakeholders Management in establishing credible relations in the Project environment.